2021
DOI: 10.1038/s41598-021-88514-y
|View full text |Cite
|
Sign up to set email alerts
|

Environmental dissemination of pathogenic Listeria monocytogenes in flowing surface waters in Switzerland

Abstract: Listeria monocytogenes is an opportunistic pathogen that is widely distributed in the environment. The aquatic environment may represent a potential source for the transmission of L. monocytogenes to animals and the food chain. The present study assessed the occurrence of L. monocytogenes in 191 surface water samples from rivers, streams and inland canals throughout Switzerland. Twenty-five (13%) of the surface water samples contained L. monocytogenes. Whole genome sequence (WGS) data were used to characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
41
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 60 publications
8
41
1
Order By: Relevance
“…Serotype 1/2a was the most prevalent (78.95%) compared to serotype 4b (21.05%). Our findings corroborated a similar report of Lm isolates recovered from surface water samples in Canada and Switzerland where strains were either serotype 1/2a or 4b (Lyautey et al, 2007;Raschle et al, 2021). By contrast, another study carried out on a municipal water supply watershed in Nova Scotia, Canada, found serotypes 4b/4d/4e as the most prevalent strains recovered from water (Stea et al, 2015).…”
Section: Frontiers In Environmentalsupporting
confidence: 91%
See 3 more Smart Citations
“…Serotype 1/2a was the most prevalent (78.95%) compared to serotype 4b (21.05%). Our findings corroborated a similar report of Lm isolates recovered from surface water samples in Canada and Switzerland where strains were either serotype 1/2a or 4b (Lyautey et al, 2007;Raschle et al, 2021). By contrast, another study carried out on a municipal water supply watershed in Nova Scotia, Canada, found serotypes 4b/4d/4e as the most prevalent strains recovered from water (Stea et al, 2015).…”
Section: Frontiers In Environmentalsupporting
confidence: 91%
“…By contrast, another study carried out on a municipal water supply watershed in Nova Scotia, Canada, found serotypes 4b/4d/4e as the most prevalent strains recovered from water (Stea et al, 2015). Our study is in support of previous studies stating that Lm serotypes usually found in various cases of human listeriosis were also found in environmental waters (Raschle et al, 2021). Notably, about 95% of Lm isolated in clinical samples belongs to serotypes 1/2a, 1/2b, 1/ 2c, and 4b (Doumith et al, 2004;Pontello et al, 2012).…”
Section: Frontiers In Environmentalsupporting
confidence: 89%
See 2 more Smart Citations
“…The widespread distribution of L. monocytogenes CC18 and CC37 in control and case farms without significant differences in their prevalence (p > 0.05) may be associated with their environmental origin. In previous studies, ST37 (CC37) was associated with ruminants, ruminant farms and wildlife environments [21,39]. CC37 was prevalent among clinical isolates from ruminant farms [40].…”
Section: Discussionmentioning
confidence: 93%